PRECISE ESTIMATION OF ROAD HORIZONTAL AND VERTICAL GEOMETRIC FEATURES USING MOBILE MAPPING TECHNIQUES - KARAMANOU, ALEXANDRA; PAPAZISSI, KALLIOPI; PAPAZISSI, KALLIOPI; PARADISSIS, DEMETRIS; PARADISSIS, DEMETRIS; PSARIANOS, BASIL; PSARIANOS, BASIL (Boletim de Ciências Geodésicas, 2009)
This paper presents a software especially developed for the precise estimation of road horizontal and vertical geometric features, using the GPS/IMU data collected during the digital survey of road nets. The survey is based upon the geodetic positioning of a suitably equipped vehicle, moving along the road in a two way journey (forward/reverse). Firstly the acquired data is used to extract the centreline of the road and at the next level the parameters of the horizontal and vertical features of the road are computed. The estimation of the parameters is based on a least squares adjustment of the characteristic curves applied on the points forming the bearing and the inclination diagram of the road, whereas the final quality check of each curve fitting is performed in the corresponding segments of the horizontal and vertical alignment. Until today the software has been successfully applied at more than 600km of the National Greek road net, while the results of the processing verify that the total reproduction of the centreline of a road can be achieved with 20cm accuracy.